IL-6 receptor antibody treatment improves muscle weakness in experimental autoimmune myasthenia gravis mouse model - Miyake, Shota; Serizawa, Kenichi; Onishi, Shinichi; Katsura, Yoshichika; Baba, Masayuki; Kurasawa, Mitsue; Tomizawa-Shinohara, Haruna; Yorozu, Keigo; Matsumoto, Yoshihiro; Noguchi-Sasaki, Mariko (Frontiers in Neurology, 2024)
Myasthenia gravis (MG) is a chronic autoimmune disease characterized by muscle weakness and fatigue. It is caused by pathological autoantibodies against components expressed at neuromuscular junctions, such as acetylcholine receptor (AChR). Interleukin-6 (IL-6) has been suggested to play a role in the pathogenesis of MG, and IL-6 receptor (IL-6R) antibody treatment may provide a novel therapeutic option. In this study, we investigated the effects of IL-6R antibody treatment in an experimental autoimmune MG (EAMG) mouse model. We demonstrated that IL-6R antibody treatment improved muscle weakness, reduced IgG deposition at neuromuscular junctions, and the levels of AChR autoantibodies in serum. In addition, follicular helper T cells and Th17, plasma cells in lymph nodes were lower in IL-6R antibody treated mice. Our findings suggest that IL-6R blockade may be a novel and effective therapeutic strategy for the treatment of MG.